'We tend to get pad happy': a qualitative study of health practitioners' perspectives on the quality of continence care for older people in hospital. Issue 2 (9th April 2021) - Percival, John; Abbott, Katharine; Allain, Theresa; Bradley, Rachel; Cramp, Fiona; Donovan, Jenny L; McCabe, Candy; Neubauer, Kyra; Redwood, Sabi; Cotterill, Nikki
Abstract : Background: Bladder and bowel control difficulties affect 20% and 10% of the UK population, respectively, touch all age groups and are particularly prevalent in the older (65+ years) population. However, the quality of continence care is often poor, compromising patient health and well-being, increasing the risk of infection, and is a predisposing factor to nursing and residential home placement. Objective: To identify factors that help or hinder good continence care for patients aged 65 years and over in hospital medical ward settings. Medical care, not surgical, was our exclusive focus. Methods: We conducted 27 qualitative interviews with nursing, medical and allied health practitioners in three hospitals. We used a purposive sample and analysed data thematically, both manually and with the aid of NVivo software. Results: Interviews revealed perspectives on practice promoting or inhibiting good quality continence care, as well as suggestions for improvements. Good continence care was said to be advanced through person-centred care, robust assessment and monitoring, and a proactive approach to encouraging patient independence. Barriers to quality care centred on lack of oversight, automatic use of incontinence products and staffing pressures. Suggested improvements centred on participatory care, open communication and care planning with a higher bladder and bowel health profile. In order to drive such improvements, hospital-based practitioners indicate a need and desire for regular continence care training. Conclusions: Findings help explain the persistence of barriers to providing good quality care for patients aged 65 years and over with incontinence. Resolute continence promotion, in hospitals and throughout the National Health Service, would reduce reliance on products and the accompanying risks of patient dependency and catheter-associated gram-negative bacteraemia. Robust assessment and care planning, open communication and regular continence care training would assist such promotion and also help mitigate resource limitations by developing safer, time-efficient continence care.